2015
DOI: 10.19082/1597
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Global Assisted Reproductive Technologies Research: a Scientometrics study

Abstract: IntroductionThis study illustrated the global contribution to assisted reproductive technologies (ARTs) research in MEDLINE database from 1998 to 2014.MethodsIn March 2015, the MEDLINE database was searched for research publications indexed under ‘reproductive techniques, assisted’ (including the following MeSH headings: in vitro fertilization [IVF]; intracytoplasmic sperm injections; cryopreservation; and ovulation induction), with the following expressions in the fields of title or abstract: intrauterine ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
2
11
0
2
Order By: Relevance
“…In the maps prepared and considering the indicators of closeness centrality and betweenness centrality, we can conclude that the thematic topics "fertilization in vitro, adverse effects, assisted reproductive techniques, and follicle" are the most valuable from the point of view of both indicators. This finding is consistent with other research ( 27 , 28 , 30 ). Some previous studies have indicated other keywords like "cell, expression”, and “woman" are important ( 26 ).…”
Section: Discussionsupporting
confidence: 94%
“…In the maps prepared and considering the indicators of closeness centrality and betweenness centrality, we can conclude that the thematic topics "fertilization in vitro, adverse effects, assisted reproductive techniques, and follicle" are the most valuable from the point of view of both indicators. This finding is consistent with other research ( 27 , 28 , 30 ). Some previous studies have indicated other keywords like "cell, expression”, and “woman" are important ( 26 ).…”
Section: Discussionsupporting
confidence: 94%
“…There are increasing numbers of couples using assisted reproductive technologies (ART) to achieve conception. This has led to more than 5 million births since the invention of this technology [ 102 ]. While ART has undoubtedly changed the lives of many, such technologies are highly expensive and have a live birth success rate of no more than ~30% [ 103 , 104 ].…”
Section: Protecting the Germline From 4hne-induced Damagementioning
confidence: 99%
“…In this context, an increasing amount of couples has turned to assisted reproductive technology (ART) to find an answer to their reproductive needs [6], using techniques such as in vitro fertilization (IVF), intracytoplasmic sperm injection (ICSI) and intrauterine insemination (IUI) [7]. This includes those couples that present chromosomal abnormalities as well.…”
Section: Introductionmentioning
confidence: 99%